Tofacitinib Efficacy/Safety in Patients with Ankylosing Spondylitis by Baseline Body Mass Index: A Post Hoc Analysis of Phase 2/3 Trials - Hillary Norton; Paula Sliwinska-Stanczyk; Tomas Hala; Bassel El-Zorkany; Lori Stockert; Rajiv Mundayat; Lisy Wang; Christopher T. Ritchlin (Rheumatology and Therapy)
Abstract Introduction We assessed tofacitinib efficacy and safety in ankylosing spondylitis (AS) by body mass index (BMI) category. Methods Data were pooled from phase 2/3 trials; analyses included patients with active AS randomized (1:1) to tofacitinib 5 mg twice daily or placebo, who were stratified by baseline BMI into < 25, ≥ 25 to < 30, and ≥ 30 kg/m2 categories. Efficacy was assessed at week 12 and safety to week 16. Results Of 370 patients, 153, 131, and 86 had a baseline BMI  of < 25, ≥ 25 to < 30, and ≥ 30 kg/m2, respectively. At baseline, patients with BMI < 25 kg/m2 were younger and more likely to be current smokers/Asian, and patients with BMI ≥ 30 kg/m2 had higher mean waist circumference/swollen joint count (SJC) and were more likely to have enthesitis, high-sensitivity C-reactive protein (hsCRP) > 5 mg/L, an inadequate response to tumor necrosis factor inhibitors (TNFi), and prior biologic disease-modifying anti-rheumatic drug (bDMARD) use versus other categories. Across categories, tofacitinib responses/improvements were greater than with placebo, except for ≥ 40% Assessment of SpondyloArthritis international Society improvement (ASAS40), ASAS partial remission, 50% improvement from baseline in the Bath Ankylosing Spondylitis Disease Activity Index score (BASDAI50), and Ankylosing Spondylitis Disease Activity Score using C-reactive protein (ASDAS-CRP) inactive disease rates, which were similar for tofacitinib and placebo in the BMI ≥ 30 kg/m2 category. Treatment effects were similar across categories, except for BASDAI50, which was smaller in the BMI ≥ 30 category versus  the < 25 kg/m2 category. More adverse events (AEs) and serious adverse events (SAEs) with tofacitinib were reported in the BMI < 25 kg/m2 category, which had a higher proportion of current smokers versus other categories. Conclusions Regardless of baseline BMI category, efficacy was greater with tofacitinib versus placebo in patients with AS, and no treatment effect differences between categories were observed, with exceptions for BMI ≥ 30 kg/m2 (more active/treatment-refractory disease and a smaller sample size). Overall, tofacitinib safety was generally comparable across categories; however, AE/SAE rates with tofacitinib were higher in the BMI < 25 kg/m2 category (which had more current smokers). This post hoc analysis demonstrates that tofacitinib can be considered as a treatment option for AS, regardless of baseline BMI category; however, interpretation was limited by small sample sizes and differences in sample sizes and baseline characteristics across categories. Trial Registration ClinicalTrials.gov identifiers, NCT01786668 and NCT03502616.